AUDIO STEGANOGRAPHY BASED ON SIGNALMODULATION IN WAVELET DOMAIN - George, Loay; Mahmood, Ghassan (Iraqi Journal of Science, 2024)
In this paper, an audio steganography system is proposed to hide a sequence ofbinary digits (bits) in digital audio data. The hiding method is based on applyingamplitude modulation technique on wavelet transform coefficients. The embeddingschema implies partitioning the audio signal (cover) into a number of non overlapslices, then the average of AC energy of all slices are examined; and the slices havethe highest energy are considered as good hosts for secret bit. The shift incoefficients values, caused by embedding process, may cause modification in theenergy status of the host slice; this problem is avoided by applying an algebraicmanipulation so as to ensure that the extraction detector can to correctly identify theaudio host slices. Bits insertion is done by transforming the selected host slices intowavelet domain using the biorthogonal tap (9\7) wavelet filters. Then, some of thehighly valued coefficients of the high frequency subband are quantized to use themto host the secret bits 0, 1 by adding or subtracting a modulation step. The testresults indicated that a perfect retrieval of secret bits could attained, while the hidingrate is small and the quality of stego objects is high.